Państwo Związkowe Białorusi i Rosji - Kakareko, Ksenia (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
Russo-Belarusian integration has assumed the form of a Union State by virtue of an agreement signed on December 8, 1999. The agreement regulated mutual relations between the states and provided concrete details of a common state, which could in the future transform into a state that would be a model illustration of the notion. The paper analyzes the stage of statehood the union state is currently at and how advanced the integration process has become.